Avaliação da enzima 3-desoxi-D-arabino-heptulosonato-7-fosfato sintase (DAHPs) como um alvo molecular vulnerável para o desenvolvimento de novos compostos antimicobacterianos - Galina, Luiza (2022)
Tuberculosis (TB) is a disease caused mainly by the bacillus Mycobacterium tuberculosis. The current treatment for TB consists of four first-line antibiotics for at least six months, which leads to adherence issues and the emergence of drug-resistant M. tuberculosis strains. Therefore, anti-TB agents effective against drug-resistant strains and more tolerable by the human host are needed. Target-based approaches to the rational drug development ought to identify potential molecular targets that are essential for the pathogen survival. Besides the target essentiality, determining the vulnerability of the target allows us to assess what level of target inhibition is necessary to impact bacterial growth. The shikimate pathway is responsible for the biosynthesis of chorismate, which is the precursor of several essential aromatic compounds required for the bacillus growth. As this metabolic pathway is absent in mammals, the shikimate pathway has been studied to identify targets to develop herbicides and antibiotics. The essentiality of the pathway in M. tuberculosis was confirmed in previous studies, indicating the enzymes present in the pathway as promising targets for the rational design of drugs. The enzyme 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase (DAHPs), encoded by the aroG gene, is responsible for the first key step of the shikimate pathway and represents a potential molecular target for inhibitors. The main objective of this thesis was to determine the vulnerability of the enzyme DAHPs from M. tuberculosis (MtbDAHPs) in different infection contexts. The results showed that the silencing of the aroG gene by the CRISPRi system is capable of inhibiting the growth of the bacillus under normal growth conditions and in infected macrophages, proving the vulnerability of aroG in the tested contexts, thereby indicating the MtbDAHPs protein as a target for the design of inhibitors and hence the development of new anti-TB agents. In addition, the study contributes to a better understanding of the biosynthesis of aromatic compounds and the bacillus physiology.